Common DRG System - the Future of Europe? A Response to Recent Commentary - Gerli Paat-Ahi (Kerman University of Medical Sciences, 2015)
This is a short piece in response to the "Heterogeneity of European DRG systems and potentials for a common EuroDRG system"1 by Alexander Geissler, Wilm Quentin and Reinhard Busse from the EuroDRG team. We would like to thank them for taking the time to read our article and offer excellent suggestions to the diagnosis-related group (DRG) systems for further development.